Outcomes and recurrence pattern analysis of intensity modulated chemoradiotherapy in nasopharyngeal cancer: a retrospective study from Heidelberg University Hospital - Bauer, Lukas; Regnery, Sebastian; Deng, Maximilian; Stritzke, Florian; Schröter, Philipp; Franke, Henrik; Netzer, Nils; Uzun-Lang, Kristin; Kozyra, Katharina; Thölken, Rubens; Debus, Jürgen; Held, Thomas (Radiation oncology, 2025)
Background: To evaluate treatment outcomes, toxicity, and recurrence patterns by dose level in nasopharyngeal carcinoma (NPC) patients treated with intensity-modulated radiotherapy (IMRT) and weekly cisplatin.Methods: We retrospectively analyzed 48 NPC patients treated between 2005 and 2019 with IMRT and weekly cisplatin (40 mg/m²). The planning target volume (PTV) received a median total dose of 57.6 Gy (1.8 Gy/fraction) with a simultaneous integrated boost to the primary tumor and nodal metastases up to 70.4 Gy. To assess recurrence patterns, follow-up imaging was deformably co-registered with planning CTs (pCT), and recurrent gross tumor volumes (rGTVs) were delineated and mapped to pCTs. Recurrences were categorized using a centroid-based system into five types: A (central high-dose), B (peripheral high-dose), C (central intermediate-/low-dose), D (peripheral intermediate-/low-dose), and E (extraneous dose). Results: With a median follow-up of 73 months (range 24–156), 9 patients (19%) had died. The 3-, 5-, and 10-year overall survival rates were 98%, 96%, and 67%, respectively. Local control rates (LCR) at 2, 3, and 5 years were 92%, 89%, and 89%; regional control was 96%, 94%, and 94%; and distant control was 92%, 89%, and 89%. Treatment was well tolerated, with no grade ≥ 4 toxicities. Grade 3 acute toxicities occurred in 23 patients (48%), most commonly dysphagia, with nearly all resolving within 90 days. Among treatment failures, distant metastases (13%) and local relapses (10%) were most frequent. Of 8 local and/or regional recurrences analyzed, 2 were type A (central high-dose), 3 type B (“marginal”), 2 type C (central intermediate-/low-dose), and 1 type E (“out-of-field”). Conclusion: IMRT with weekly cisplatin yields excellent survival and locoregional control with acceptable toxicity in NPC. Distant metastasis as one of the predominant failure patterns highlights the need for more effective systemic therapies. Most local recurrences arose within high-dose areas, suggesting a potential opportunity for treatment optimization.
Veröffentlicht: 08. Dezember 2025
Gesehen am 26.02.2026